Mechanistic Studies on Photoacylation - Megawati Santoso (Institut Teknologi Bandung, 1997)
An unprecedented photoacylation method for preparation of acyl- and aroyliron(III) porphyrin complexes has been reported1). This paper present the mechanistic studies on such photoacylation. Detailed mechanistic studies on the photoacylation of chloroiron(III) tetraphenylporphyrin ((TPP)FeCl) suggest